1994
DOI: 10.1111/j.1445-5994.1994.tb04419.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal coronary angioplasty: clinical and quality of life outcomes one year later

Abstract: These findings suggest that, after PTCA, the majority of patients experienced improved quality of life which was sustained one year later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Compared to earlier studies, we found a substantially higher number of sick-leave days following coronary revascularisation [3][8], [10], [19]. Among the CABG patients, 34% among the women and 24% among the men were sickness absent for at least 365 days after the intervention and for the PCI patients the corresponding figures were 24 and 14%, respectively.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Compared to earlier studies, we found a substantially higher number of sick-leave days following coronary revascularisation [3][8], [10], [19]. Among the CABG patients, 34% among the women and 24% among the men were sickness absent for at least 365 days after the intervention and for the PCI patients the corresponding figures were 24 and 14%, respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…Among patients working, most return to work after PCI and CABG; faster after PCI [3], [8], [11], [13]. Only few studies on sickness absence after coronary revascularisation have been performed in Sweden and none of them presented gender specific results [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The median time of sick leave was 25 days (13). After one year, 79% of all patients were still working.…”
Section: Sick Leave In Patients Following Pci or Cabg (Table 8iii)mentioning
confidence: 99%
“…As with myocardial infarction studies, there are three main groups: descriptive, predictive, and interventional regarding both type of coronary artery intervention and aftercare. In three studies (13,29,30) the outcome is described during the first year following the intervention, and six studies (24, 31 -35) investigated the predictors for RTW following the intervention. Seven studies (12, 14, 36 -40) compared the results between patients after PCI or CABG, and four studies (41 -44) described the outcome of rehabilitation programmes.…”
Section: Sick Leave In Patients Following Pci or Cabg (Table 8iii)mentioning
confidence: 99%
“…This implies that focus on rehabilitation and reintegration into the workforce becomes increasingly important. Previous studies have described that around 60-80 % of the patients in the working age return to work after coronary heart disease [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%